Perception of university teachers and students about early training in scientific research - Medina Morales, Gladys del Carmen (2020)
Results of the institutional program are presented at the Universidad Juárez Autónoma de Tabasco (UJAT), called Research Summer Program. The purpose of the study was to identify the perception that students and researchers had about themselves and each other as collaborators in the program and from there, enrich their strategies and mechanisms. The study design was descriptive where a survey was applied as an instrument for data collection. The survey consisted of 9 items for the researcher and 6 for the students. The participants were 1581 researchers (M= 851 W= 730) and 3,046 students (M= 1194 W= 1852) from the 12 academic divisions, who participated in the Research Summer Program from 2016 to 2020. The results showed a positive evaluation of the program, the role of researcher in general, as well as women’s preponderant participation, however, it was concluded to make a proposal to the corresponding instances to create a profile of the researcher, as well as to reformulate methodologies, evaluation instruments that yield data that allow to improve the traceability of the scientific training that is offered to students in that institution.